A corpus-based study of similes and cognate adjectival forms in English, Swedish and Croatian - Novoselec, Zvonimir (Array, 2012)
This paper deals with the relationship between conventionalized similes with the structure (as) + adjective + as + NP in English, Swedish and Croatian (e.g. (as) clear as crystal, tung som bly (‘heavy as lead’), hladan kao led (‘cold as ice’)) and cognate adjectival forms, more specifically noun-adjective compounds such as crystal-clear and blytung (‘lead heavy’) and adverb + adjective collocations such as ledeno hladan (lit. icily cold). Using corpus data, we examine the frequencies, collocational range and meaning of similes and adjectival forms in order to determine the degree of conventionality of each type of item and to identify the mechanisms underlying the process of creation of adjectival forms in the three languages. The aim is to show that similes and adjectival forms should be viewed on a scale of conventionality and grammaticalization. The frequencies of the two types of items as well as their semantic and syntactic differences raise the issue of the status of adjectival forms as idiomatic expressions, and the issue of items which are listed in dictionaries as canonical forms.